VD_FINDINFO HC / 2014 / 928 vom 27. November 2014 - VD Tribunal cantonal (2014)
EXÉCUTION FORCÉE, EXPULSION DE LOCATAIRE, SOUS-LOCATAIRE, MOYEN DE DROIT | 309 let. a CPC (CH), 319 let. a CPC (CH), 341 CPC (CH), 346 CPC (CH)